2017
DOI: 10.1039/c7ra01269a
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled carbon nanotube-supported CuCo2S4 as a heterogeneous Fenton-like catalyst with enhanced performance

Abstract: In this paper, we prepared CuCo 2 S 4 /MWCNTs as a heterogeneous iron-free bimetal catalyst for the degradation of methylene blue (MB) dye by uniformly synthesizing CuCo 2 S 4 nanoparticles on the surfaces of multiwalled carbon nanotubes (MWCNTs). The homogeneous nanostructure, tuned by MWCNTs, and the efficient electron transfer from CuCo 2 S 4 to MWCNTs resulted in a quite decent catalytic activity, which was superior to that of pristine CuCo 2 S 4 and monometal sulfides. Moreover, CuCo 2 S 4 /MWCNTs maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Also, larger quantities of • CO 2 – were produced with prolonged irradiation time (Figure D), as well as with concomitant Co 2+ and Cu 2+ (Figure B), in accordance with the observation that an UV exposure time of 60 s was necessary for efficient PCVG of Mo. Such a synergistic effect of two or more kinds of metals, not surprisingly, was found in heterogeneous di- or polymetal oxides (Ce–Mn, Co–Cu) and sulfides (Ni–Mo, Co–Cu) possessing outstanding catalytic or electrochemical properties and proposed for treatment of dye-containing wastewater as an alternative iron-free Fenton catalyst . With respect to the homogeneous PCVG reactions, abundant reactive free radicals (e.g., • OH and • CO 2 – as trapped by DMPO) were produced, and thus it was highly possible to generate a thermodynamically favored Cu­(I)/Co­(III) redox couple other than Cu­(I)/Cu­(II) and Co­(II)/Co­(III), which in turn accelerated the photolysis of formic acid.…”
Section: Resultssupporting
confidence: 84%
“…Also, larger quantities of • CO 2 – were produced with prolonged irradiation time (Figure D), as well as with concomitant Co 2+ and Cu 2+ (Figure B), in accordance with the observation that an UV exposure time of 60 s was necessary for efficient PCVG of Mo. Such a synergistic effect of two or more kinds of metals, not surprisingly, was found in heterogeneous di- or polymetal oxides (Ce–Mn, Co–Cu) and sulfides (Ni–Mo, Co–Cu) possessing outstanding catalytic or electrochemical properties and proposed for treatment of dye-containing wastewater as an alternative iron-free Fenton catalyst . With respect to the homogeneous PCVG reactions, abundant reactive free radicals (e.g., • OH and • CO 2 – as trapped by DMPO) were produced, and thus it was highly possible to generate a thermodynamically favored Cu­(I)/Co­(III) redox couple other than Cu­(I)/Cu­(II) and Co­(II)/Co­(III), which in turn accelerated the photolysis of formic acid.…”
Section: Resultssupporting
confidence: 84%
“…Serp et al studied the catalytic performance of carbon nanotubes and carbon nanofibers and found that CNTs were promising and competitive supports as compared with carbon nanofibers because of their large surface area, stability, and adsorption properties. Lately, Zhang et al investigated the degradation of methylene blue dye over iron‐metal‐free bicatalysts of CuCo 2 S 4 and CuCo 2 S 4 /MWCNTs composite. They found that the combination of CuCo 2 S 4 with MWCNTs gave rise to yield a promising heterogeneous Fenton‐like catalyst used in dye‐contaminated wastewater without any pH limitations.…”
Section: Introductionmentioning
confidence: 99%
“…≡Co 2+ was reacted similarly to ≡Cu + as equation ( 3) and (4). In acidic condition, H + in the system enhanced production of •OH and •OOH as equation ( 1), ( 3) and (6). •OH and •O 2oxidized MB to degradation product as equation ( 7) and (8).…”
Section: Effect Of Phmentioning
confidence: 99%
“…CuCo 2 S 4 has provided multiple redox stage leading to benefit reaction process. [6] LDH containing heterostructure have attracted attention because the composites can keep characteristic of each component, enhance catalytic activity and increase the whole properties of the composites. [7] In this work, CuCo 2 S 4 /NiFe LDH composites were fabricated by hydrothermal method.…”
mentioning
confidence: 99%